The Integration of Hadith Values and Local Culture in The Islamization of The Bugis, Makassar, and Mandar Peoples of South Sulawesi: Integrasi Nilai-Nilai Hadis dan Budaya Lokal dalam Islamisasi Masyarakat Bugis, Makassar, dan Mandar di Sulawesi Selatan - Ismail, Muhammad; Munzir, Muhammad; Amiruddin, Muhammmad Majdy; Busrah, Zulfiqar; Abdurrahman (STAIN Majene, 2025)
This study examines the integration of hadith with the local cultures of the Bugis, Makassar, and Mandar communities in the Islamization of South Sulawesi. Unlike previous research that predominantly focuses on the historical or political dimensions of Islamization, this study highlights how the core principles of the Prophet Muhammad’s da‘wah—particularly gentleness (rifq), ease (taysīr), wisdom (ḥikmah), and gradualism (tadarruj)—were translated by early scholars into culturally resonant practices. Employing a qualitative descriptive approach, this research analyzes hadith texts, historical sources, ethnographic studies, and empirical data from the da‘wah practices of influential figures : Datuk ri Bandang, Datuk Patimang and Datuk ri Tiro. The findings reveal that Islam was embraced peacefully due to the deep compatibility between Prophetic ethical principles and local cultural values such as siri’ (honor), pacce (solidarity), and sipakatau (human dignity). This harmony is reflected in the Islamized forms of communal traditions, including mabbarazanji, sayyang pattu’du, and other ritual expressions. The study concludes that the success of Islamization in South Sulawesi resulted from adaptive, persuasive, and context-sensitive da‘wah strategies rooted in the Sunnah. These findings offer a compelling model of hadith-based cultural da‘wah that remains highly relevant for contemporary multicultural societies.